Perancangan dan Implementasi Sistem PLTS Off-Grid pada Gerobak Bakso: : Solusi Efisiensi Energi dan Mobilitas - Enggri, Enggri Vristanto; Siswanto, Diky; Setiawidayat, Sabar (JASEE Journal of Application and Science on Electrical Engineering, 2025)
This study investigates the design and implementation of an off-grid solar photovoltaic (PV) system for a meatball cart as a renewable energy solution for small mobile food businesses that still commonly rely on conventional energy sources for lighting and heating. The developed system integrates a 120 Wp monocrystalline PV module, a 12 V 100 Ah LiFePO4 battery, a PWM solar charge controller, a 1000 W inverter, and an automatic soup-heating subsystem based on a DS18B20 temperature sensor, thermocontroller, and solid-state relay. Field testing was conducted on a meatball cart in Pakis District, Malang Regency, for two weeks of operation. The results show that the system was functionally able to operate the supporting loads and maintain soup temperature within 85–95°C through automatic switching control. However, the total daily load of 3810 Wh was still higher than the available daily energy of about 1920 Wh. This finding indicates that the current configuration is feasible as an implementation prototype but has not yet achieved fully autonomous full-load operation. Overall, the study demonstrates the potential of integrating off-grid PV and closed-loop thermal control to reduce dependence on fossil energy and improve the operational flexibility of micro-enterprises.